Reflection and anomalous behavior of refractive index in defect photonic band gap structure - Srivastava S.K.; Ojha S.P. (My University, 2025)
This paper describes the reflectivity properties of layer-by-layer-based photonic band gap (PBG) structures with a defect in their normal structures. The defect is created by the removal of a single material slab. To calculate reflectivity, we use a 2 × 2 matrix formulation. The defective PBG structure gives nearly 100% reflections in the near-infrared region in addition to some parts of the visible region of the wavelengths for all possible angles, and thus acts as broadband reflector. Also, we study the anomalous behavior of the refractive index in these structures and find that the effective refractive index neff ≪ 1 nears the band edges. © 2003 Wiley Periodicals, Inc.